TOWARDS AN ABM-BASED FRAMEWORK FOR INVESTIGATING CONSUMER BEHAVIOUR IN THE INSURANCE INDUSTRY - Ulbinaitė, Aurelija; Moullec, Yannick Le (Ekonomika, 2010)
This paper presents a framework that builds upon agent-based modelling for investigating the behaviour of consumers in the insurance industry. Consumers are modelled as agents and clustered in groups reflecting their income levels. Agents that model consumers are characterised by their socio-demographic features and interact with other insurance consumer-agents by means of local and global social networks. Furthermore, the environment in which they evolve models the impact of external factors such as mortality, disease and other accident rates as well as insurance culture. This makes that consumer-agents accumulate experience, improve their understanding and knowledge of financial products, and thus develop their perception of need for security and consider the usefulness of insurance services. In turn, the framework enables to model the construction of the customers’ insurance product purchase decision. p>